EXCHANGE RATE AS A MODERATOR IN THE RELATIONSHIP BETWEEN LIQUIDITY AND LEVERAGE ON STOCK RETURNS - Sohipa Asazdia Abdullah; Mohamad Agus Salim Monoarfa; Idham Masri Ishak (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to examine the effect of the Current Ratio (CR) and Debt to Equity Ratio (DER) on stock returns, with the exchange rate as a moderating variable, in retail sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This research employed a quantitative approach using secondary data obtained from annual financial reports and stock price data. The sampling technique used purposive sampling, resulting in 25 companies with 125 observations. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that the Current Ratio has a negative and significant effect on stock returns, meaning that excessively high liquidity tends to reduce stock returns. Debt to Equity Ratio also has a negative and significant effect on stock returns, indicating that higher leverage increases financial risk and lowers investor confidence. Simultaneously, Current Ratio and Debt to Equity Ratio significantly affect stock returns. However, the exchange rate has no effect on stock returns. Furthermore, the exchange rate is unable to moderate the relationship between Current Ratio and stock returns, as well as between Debt to Equity Ratio and stock returns. These findings imply that internal company factors, particularly liquidity management and capital structure, are more dominant in influencing stock returns than external macroeconomic factors such as exchange rate fluctuations. Therefore, investors are advised to pay closer attention to financial fundamentals when making investment decisions in the retail sector.